Chapter «Quel nome pernicioso di nobile»: Uberto Foglietta e la nobiltà di Genova fra tardo medioevo e prima età moderna - Castelnuovo, Guido (Reti Medievali E-Book, 2021)
The present contribution aims at discussing the many late medieval and early modern interpretations elaborated in urban and (post)communal Italy on nobility. It does so by attentively analysing the first book of the La Repubblica di Genova, written around 1550 by Uberto Foglietta, a Genoese patrician and a future historian of the city. Foglietta's libello therefore is a good starting point to reinterpret the vexata quaestio of being noble both in 16th century Genoa, and in the broader context of Renaissance Italian urban culture.